"OMG, I Get Like 100 Teaspoons of Sugar a Day!" Rural Teens' Grasp of Their Beverage Consumption Habits. Issue 4 (July 2022) - Lilo, Emily A.; West, Andrew
As part of a campaign to encourage healthier beverage consumption in a rural New Mexico high school, we wanted to understand students' perceptions of their habits, and the associated health risks and benefits surrounding water and sugar-sweetened beverage consumption to influence future messaging to change behavior. We conducted a posthoc qualitative analysis of 27 student interviews from the program evaluation with both students who participated in the campaign and those who did not. Pre-campaign, students appeared largely unaware of the health risks posed by their beverage consumption habits, lacking any knowledge of nutritional recommendations, water recommendations, or of the sugar levels in products. When informed of the risks, students expressed concern for themselves, their family members, and friends, indicated a desire to make significant changes, and reported making changes for themselves, and educating others regarding the risks. Given the large amounts of money spent and concentrated efforts focused on marketing SSBs to teens, it is critically important to be educating teens and engaging them in behavior change strategies. These data can inform future strategies to improve teen health behaviors and encourage teens to become family health messengers for obesity and diabetes prevention.